Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

rearrange the quadratic equation so that it is equal to 0 then factor the equation x^2-4x=-2x+24

Sagot :

naǫ
[tex]x^2-4x=-2x+24 \\ x^2-4x+2x-24=0 \\ x^2-2x-24=0 \\ x^2-6x+4x-24=0 \\ x(x-6)+4(x-6)=0 \\ \boxed{(x+4)(x-6)=0} \hbox{ - factored equation} \\ (x+4)(x-6)=0 \\ x+4=0 \ \lor \ x-6=0 \\ x=-4 \ \lor \ x=6 \\ x=-4 \hbox{ or } x=6 [/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.